Solve by factoring: x2 + 5x = −6

x^2 + 5x + 6 = 0

2+3 = 5 and 2x3 = 6

so (x-2)(x-3) = 0

then x-2=0 or x-3 = 0

x = 2 or x = 3

Did I do this right??

1 answer

(x+2)(x +3) = 0
x +2 = 0
x+ 3 = 0
x = -2
x = -3
Similar Questions
  1. My bad I didn't save this questions link:Solve by factoring. x² - 121 = 0 0 -11 11 11, -11 Solve by factoring. m² + 8m + 7 = 0
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. KUTA SOFTWARE- INFINITE ALGEBRA 1SOLVING QUADRATIC EQUATIONS BY FACTORING SOLVE EACH EQUATION BY FACTORING. 1) (K+ 1) (K - 5) =
    1. answers icon 1 answer
  3. Solve by factoring 2w^2-11=-12I'm having a super hard time with factoring....can someone plz help?
    1. answers icon 2 answers
more similar questions